Ludy tubylcze w relacjach Liwiusza i Pompejusza Trogusa/Justyna o wyprawie do Italii Aleksandra z Epiru = Indigenous peoples in the accounts of Livy and Pompeius Trogus/Justin on Alexander of Epirus's expedition to Italy - Pawlak, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Alexander of Epirus arrived in Italy in 334/333 BC to support Taranto in fighting the natives. The most comprehensive descriptions of this expedition are found in the works of Livy and Pompeius Trogus (known to us through Justin). The main opponents of Alexander were the Lucanians and Bruttians, against whom he fought and was successful - conquering their cities and defeating the combined Lucanian-Samnite forces in the battle near Paestum.
Keywords: Titus Livius (59 p.n.e.- 17 n.e.); Pompejusz Trogus (historyk rzymski; I w. p.n.e. - I w. n.e.); Justyn; Aleksander I Epirota (król Epiru; 372-330 p.n.e.); Tarent; Lukanowie; Bruttiowie; Messapiowie; Samnici; Justin; Alexander of Epirus; Taranto; Lucanians; Bruttians; Messapians; Samnites